Assessing Impulsivity in Chinese: Elaborating Validity of BIS Among Male Prisoners - Wang, Meng-Cheng (Criminal justice and behavior, 2018)
This study was carried out to test the factor structure and psychometric properties of the Barratt Impulsiveness Scale-Version 11 (BIS-11), and its short versions (the eight-item and 15-item BIS) in a sample of 424 Chinese male prisoners (M = 31.26, SD = 7.43, age = 18-52 years). Confirmatory factor analysis (CFAs) indicated that the single-factor model of BIS with eight items (BIS-8) and the three-factor model of BIS with 15 items (BIS-15) fit the data well. In addition, the item response theory (IRT) approach confirmed the construct and items for the BIS-8 with good discrimination, threshold parameters, and test information curve. Correlations with psychopathic traits, antisocial personality disorder, and aggression suggested that the performance of the eight-item BIS was comparable with that of the original 30-item BIS in measuring general impulsivity.